CT features using in differentiating pleural exudates from transudates - Piyavisetpat, Nitra; Kittisatra, Khanitha (Chulalongkorn Medical Journal, 2023)
Background : Pleural effusion is one of the most frequent findings of thoracic abnormality, detected by computed tomography (CT). Differentiation between exudative from transudative effusions is crucial for diagnosis of various pathologies. Objective : To determine the accuracy of computed tomography in enabling differentiation of pleural exudates from transudates. Setting : King Chulalongkorn Memorial Hospital. Research design : A retrospective study. Patients : Patients who had pleural effusions and underwent CT of thorax and thoracentesis within 14 days of each other from March 2005 to August 2007 were recruited. Methods : We analyzed 41 pleural effusions in 41 patients. Effusions were classified as transudates or exudates using laboratory markers based on Light’s criteria. All CT scans were reviewed for the mean CT attenuation values and distribution of an effusion, the presence and appearance of pleural thickening, thickening and increased attenuation of extrapleural fat. Results : Thirty-four effusions were exudates, and 7 were transudates. The optimal threshold value was determined to be 11.75 HU for differentiation of pleural exudates. The mean attenuation value of exudates (14.8 ± 5.8 HU) was higher than transudates (10.7 ± 5.1 HU), but there was no detected significant difference (p = 0.09). Loculation of pleural effusion was found in 52.9% of exudates, with 53% sensitivity, 100 % specificity and 61% accuracy. Pleural thickenings were found in 61.8% of exudates and in 14.3% of transudates, with 62% sensitivity, 86% specificity and 66% accuracy. Extrapleural fat was thickened in 29.4% of exudates, and 64.7% of transudates. The attenuation of extrapleural fat was increased in 64.7% of exudates and 28.6% of transudates. None of transudates had loculated effusion, nodular pleural thickening nor thickening of extrapleural fat. The sensitivity, specificity and accuracy of extrapleural fat thickening were 29%, 100% and 41%; and of increased attenuation of extrapleural fat were 65%, 71% and 66%, respectively. Conclusion : Loculation of pleural effusion, nodular pleural thickening and thickening of extrapleural fat at contrast-enhanced CT are highly suggestive of the presence of pleural exudates. CT attenuation values of exudates are higher than transudates, but there were no clinical value in differentiating exudates from transudates.